Price Setting Rules, Rounding Tax, and Inattention Penalty - Doron Sayag; Avichai Snir; Daniel Levy (ZBW - Leibniz Information Centre for Economics, 2024)
We study Israel's “price rounding regulation” of January 1, 2014, which outlawed non-0-ending prices, forcing retailers to round 9-ending prices, which in many stores comprised 60%+ of all prices. The regulation's goals were to eliminate (1) the rounding tax—the extra amount consumers paid because of price rounding (which was necessitated by the abolition of low denomination coins), and (2) the inattention tax—the extra amount consumers paid the retailers because of their inattention to the prices' rightmost digits. Using 4 different datasets, we assess the government's success in achieving these goals, focusing on fast-moving consumer goods, a category of products strongly affected by the price rounding regulation. We focus on the response of the retailers to the price rounding regulation and find that although the government succeeded in eliminating the rounding tax, the bottom line is that shoppers end up paying more, not less, because of the regulation, underscoring, once again, Friedman's (1975) warning that policies should be judged by their results, not by their intentions.
Keywords: E31; K00; K20; L11; L40; L51; M30; 330; Price Rounding; Price Rounding Regulation; Regulation; Rounding Tax; Inattention; Inattention Penalty; Round Prices; 9-Ending Prices; Psychological Prices; Just Below Prices; Price Setting; Price Adjustment; Pricing; Inflation